Titania as a driving agent for DHICA polymerization: a novel strategy for the design of bioinspired antimicrobial nanomaterials1. Issue 14 (14th April 2015) - Vitiello, Giuseppe; Pezzella, Alessandro; Zanfardino, Anna; Varcamonti, Mario; Silvestri, Brigida; Costantini, Aniello; Branda, Francesco; Luciani, Giuseppina
<x xml:space="preserve">Abstract</x> Organic materials are widely employed to tune surface chemistry and/or as structuring agents of inorganic materials.